Facile synthesis of magnetic Fe3O4@BiOI@AgI for water decontamination with visible light irradiation: Different mechanisms for different organic pollutants degradation and bacterial disinfection - Jialiang Liang; Fuyang Liu; Mian Li; Liu, Wen; Meiping Tong (Water Research, 2018)
Abstract Magnetic Fe3O4@BiOI@AgI (FBA) spheres were synthesized through a multi-step process. The fabricated photocatalysts were characterized by different techniques. To testify the visible light driven photocatalytic activity of FBA, Rhodamine B and Bisphenol A were chosen as model common and emerging organic contaminants, respectively. While, gram-negative strain Escherichia coli was selected as model waterborne bacteria. The results showed that under visible light irradiation, \FBA\ contained strong photocatalytic degradation capacity towards both RhB and BPA. Moreover, \FBA\ was also found to exhibit excellent disinfection activity towards E. coli. The photocatalytic mechanisms for different pollutants by \FBA\ were determined and found to vary for different pollutants. Specifically, scavenger experiments, degradation intermediates determination, as well as theoretical density functional theory (DFT) analysis showed that RhB and \BPA\ were degraded via photosensitization (dominated by e- and ·O2−) and direct photocatalytic oxidation (contributed by h+, e- and ·O2−), respectively. Whereas, E. coli cells yet were found to be inactivated by the generation of e- and ·O2− rather than by the released Ag+. Since it contained superparamagnetic property, \FBA\ could be easily separated from the reaction suspension after use. Due to the excellent photo stability, \FBA\ exhibited strong photocatalytic activity in the fourth reused recycle. Therefore, \FBA\ could serve as a promising alternative for water purification.
Keywords: Reusability